Letter to Dr. Daniel and Jane Tolmach from Senator Alan Cranston - Alan Cranston:::::: (1976)
This letter dated February 4, 1976, is from U.S. Senator Alan Cranston to Dr. and Mrs. Dan M. Tolmach in Oxnard, California. Cranston thanks Jane and Dan Tolmach for their thoughtful holiday greetings and expresses appreciation for their goodwill and encouragement. He notes that their support provides strength as he faces the challenges and opportunities of the new year. The letter conveys warm personal regard and best wishes for 1976. A handwritten note at the bottom adds a more personal message, expressing hopes that things are going well and acknowledging the busy pace of the time.